Rabies Prevention and Management of Cats in the Context of Trap–Neuter–Vaccinate–Release Programmes. (17th July 2013) - Roebling, A. D.; Johnson, D.; Blanton, J. D.; Levin, M.; Slate, D.; Fenwick, G.; Rupprecht, C. E.
Summary Domestic cats are an important part of many Americans' lives, but effective control of the 60–100 million feral cats living throughout the country remains problematic. Although trap–neuter–vaccinate–return (TNVR) programmes are growing in popularity as alternatives to euthanizing feral cats, their ability to adequately address disease threats and population growth within managed cat colonies is dubious. Rabies transmission via feral cats is a particular concern as demonstrated by the significant proportion of rabies post‐exposure prophylaxis associated with exposures involving cats. Moreover, TNVR has not been shown to reliably reduce feral cat colony populations because of low implementation rates, inconsistent maintenance and immigration of unsterilized cats into colonies. For these reasons, TNVR programmes are not effective methods for reducing public health concerns or for controlling feral cat populations. Instead, responsible pet ownership, universal rabies vaccination of pets and removal of strays remain integral components to control rabies and other diseases.